Effect of mind-body exercise on risk factors for metabolic syndrome including insulin resistance: a meta-analysis - Li, Shufan; Wang, Peng; Wang, Jing; Zhao, Jinlei; Wang, Xing; Liu, Tong (Frontiers in Endocrinology, 2024)
Objective: To systematically evaluate the effects of mind-body exercise on risk factors of metabolic syndrome such as insulin resistance. Methods: Web of Science, PubMed, The Cochrane Library, EBSCO host, Embase, China Knowledge Network, China Biomedical Literature Database, Wanfang, and VIP were searched for the period from the establishment of the database to 1 July 2023, and randomized controlled trials of mind-body exercise interventions in patients with metabolic syndrome were collected. We applied the Cochrane Risk of Bias tool RoB2 to evaluate the methodological quality of the included literature and used RevMan5.4 software and Stata15.1 for statistical analysis. Results: A total of 14 randomized controlled trials with 1148 patients were included in this study. Meta-analysis showed that mind-body exercise significantly improved insulin resistance (SMD=-0.78, 95% CI: [-1.13, -0.43], P<0.0001), waist circumference (SMD=-2.20, 95% CI: [-3.34, -1.06], P=0.0001), body mass index (SMD=-1.50, 95% CI: [-2.03, -0.97], P<0.00001), systolic blood pressure (SMD=-3.65, 95% CI: [-5.56, -1.74], P=0.0002), diastolic blood pressure (SMD=-3.32, 95% CI: [- 3.77, -2.87], P<0.00001), fasting blood glucose (SMD=-0.57, 95% CI: [-0.99, -0.15], P=0.008), triglycerides (SMD=-0.27, 95% CI: [-0.46, -0.08], P=0.004), high-density lipoprotein cholesterol (SMD=0.58, the 95% CI: [0.28, 0.87], P=0.0001). Subgroup analysis showed that the intervention programme with exercise form of fitness qigong, exercise cycle of 24-48 weeks, and exercise frequency of 6-7 times/week could significantly improve each risk factor. Conclusion: Mind-body exercise is effective in improving risk factors in patients with metabolic syndrome. Current evidence recommends an intervention program of low to moderate intensity fitness qigong, with 6-7 sessions per week for 24-48 weeks in patients with metabolic syndrome.